From GSM to LTE-advanced : an introduction to mobile networks and mobile broadband - Sauter, Martin (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
This revised edition of Communication Systems from GSM to LTE: An Introduction to Mobile Networksand Mobile Broadband Second Edition (Wiley 2010) contains not only a technical description of thedifferent wireless systems available today, but also explains the rationale behind the different mechanisms and implementations; not only the 'how' but also the 'why'. In this way, the advantages and also limitations of each technology become apparent. Offering a solid introduction to major global wireless standards and comparisons of the different wirelesstechnologies and their applications, this edition has been updated to provide the latest directions andactivities in 3GPP standardization up to Release 12, and importantly includes a new chapter on Voiceover LTE (VoLTE). There are new sections on Building Blocks of a Voice Centric Device, Building Blocks of a Smart Phone, Fast Dormancy, IMS and High-Speed Downlink Packet Access, and Wi-Fi-Protected Setup. Other sections have been considerably updated in places reflecting the current state of the technology. Describes the different systems based on the standards, their practical implementation and design assumptions, and the performance and capacity of each system in practice is analyzed and explained Questions at the end of each chapter and answers on the accompanying website make this book ideal for self-study or as course material.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mobile communication systems; Wireless metropolitan area networks; Wireless LANs; Mobile communication systems; Wireless Metropolitan Area networks; Wireless LANs; TECHNOLOGY & ENGINEERING -- Mechanical; Mobile communication systems; Wireless LANs; Wireless metropolitan area networks; Mobile communication systems; Wireless metropolitan area networks; Wireless LANs; Electronic books; Electronic books